2018
DOI: 10.1371/journal.pone.0192003
|View full text |Cite
|
Sign up to set email alerts
|

The Mexican bean beetle (Epilachna varivestis) regurgitome and insights into beetle-borne virus specificity

Abstract: For nearly 400 million years, insects and plants have been embattled in an evolutionary arms race. Insects have developed diverse feeding strategies and behaviors in an effort to circumvent and overcome an extensive collection of plant defense tactics. Sap-sucking insects often inject saliva into hosts plants, which contains a suite of effector proteins and even microbial communities that can alter the plant’s defenses. Lacking salivary glands, leaf-feeding beetles represent an interesting group of phytophagou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 74 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…We observed relatively few bacterial taxa associated with the regurgitant of fall armyworm. A recent study of the “regurgitome” of Mexican bean beetle ( Epilachna varivestis ) revealed a highly diverse microbiome with 1230 bacterial species in 577 genera 58 . In our study we observed less diversity and richness; culture-independent sequencing detected about 100 OTUs in larvae fed on maize and soybean.…”
Section: Discussionmentioning
confidence: 99%
“…We observed relatively few bacterial taxa associated with the regurgitant of fall armyworm. A recent study of the “regurgitome” of Mexican bean beetle ( Epilachna varivestis ) revealed a highly diverse microbiome with 1230 bacterial species in 577 genera 58 . In our study we observed less diversity and richness; culture-independent sequencing detected about 100 OTUs in larvae fed on maize and soybean.…”
Section: Discussionmentioning
confidence: 99%
“…We observed relatively high bacteria taxa associated within the gut of fall armyworm fed with different host plants ranging from 205-416 species in 319 -578 genera from 511-1518 OTUs. Similarly, a recent study of the of Mexican bean beetle (Epilachna varivestis) regurgitant revealed a highly diverse microbiome with 1230 bacterial species in 577 genera [52] However, Jones et al [53] reported less diversity and richness using culture dependent sequencing which detected about 100 OTUs in fall army larvae fed on maize and soybean. Bacteria associated with insects can confer their host with traits that allow them to exploit different host plant species in diverse ways, further de ning the species host range [3] Shin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Ingested pathogen circulates within the insect body, reaches the salivary glands, mouthparts, and finally enters the plant host through the wounds resulting from insect feeding. Overall, insects can carry plant pathogens externally on their legs, mouthparts, bodies, and internally in their digestive tract, and hemocoel (Figure 2; Agrios, 2008;Gedling et al, 2018).…”
Section: Mechanism Of Plant Pathogens Transmissionmentioning
confidence: 99%
“…It is estimated that beetles transmit approximately 11% of insect-borne viruses (Smith et al, 2017;Bhat and Rao, 2020). Beetle vectors of plant viruses belong to Chrysomelidae, Coccinellidae, Curculionidae, Meloidae families (Gergerich, 2001;Fereres and Raccah, 2015) and have a unique mode of transmission of at least six groups of plant virus genera: Machlomovirus, Bromovirus, Carmovirus, Comovirus, Sobemovirus, and Tymovirus (Scott and Fulton, 1978;Gedling et al, 2018). Mechanisms of virus acquisition and transmission are associated with the fact that most of the beetle vectors eat plant cells between the leaf veins and regurgitate during feeding, bathing their mouthparts with sap and virus particles, therefore beetle-associated viruses can be deposited into a chewing wound.…”
Section: Beetles As Reservoirs and Vectors Of Virusesmentioning
confidence: 99%
See 1 more Smart Citation